Pengaruh Lama Presto dan Konsentrasi Natrium Bikarbonat (NaHCO3) terhadap Karakteristik Tepung Tulang Ikan Tenggiri (Scomberomorus commerson) - Eris Fianty; Yulia Oktavia; Made Suhandana (Universitas Sriwijaya, 2021)
Most fish processing industries only use fish meat as raw material for industry. Whereas fish bones are contain high mineral content needed by the human body and can be utilized as high calcium fishbone meal. Fishbone meal in this reaseach was made from waste from the fishery industries in Tanjungpinang, Riau Islands. Mackerel fishbone meal was made in several steps consist of preparation of raw materials, boiling of fishbones, washing and cleaning of the bones, presto processing of fish bones with the addition of sodium bicarbonate (NaHCO3), drying, siege and sieving. The purpose of this study is to determine the effect of presto duration and concentration of NaHCO3. This research was conducted by the factorial randomized block design method (RAKF) with two factors: duration of presto (2 hours (P1) and 4 hours (P2)) and concentration of NaHCO3 (0% (N1), 1% (N2) and 2% (N3)). The results showed that the duration of presto treatment and the concentration of sodium bicarbonate (NaHCO3) had a significant effect on the 5% level of yield but not significant on calsium content. The best results showed on 2 hours presto with addition NaHCO3 1%. The best treatment was used as a sample to measure the chemical characteristics of mackerel fish bone meal. Fish bone meal obtained 4.86% water content, 69.84% ash content, 3.72% protein content, 17.21% fat content, 12.56% phosphorus content, and 0.46% crude fiber. The chemical content of fishbone meal has been appropriate with Indonesian Nasional Standard.